Accessory pathway‐related left ventricular wall motion abnormality and the effects of radiofrequency catheter ablation in patients with Wolff‐Parkinson‐White syndrome. (22nd October 2018) - Uhm, Jae‐Sun; Nam, Jong‐Ho; Yu, Hee Tae; Yang, Pil‐Sung; Kim, Tae‐Hoon; Cho, In‐Jeong; Shim, Chi Young; Joung, Boyoung; Hong, Geu‐Ru; Pak, Hui‐Nam; Lee, Moon‐Hyoung
Abstract: Introduction: The objective of the current study was to elucidate the effects of the accessory pathways (APs) on the left ventricular (LV) wall motion and radiofrequency catheter ablation (RFCA) on AP‐related regional wall motion abnormality (RWMA) in patients with Wolff‐Parkinson‐White (WPW) syndrome. Methods and Results: We included 348 consecutive patients (age, 37.6 ± 17.3 years; men, 58.3%) with WPW syndrome who underwent RFCA for AP. We analyzed electrocardiographic data, the AP location, LV ejection fraction (LVEF), and RWMA patterns and their changes after RFCA. The locations of APs were right, septal, and left in 78, 94, and 176 patients, respectively. RWMA at the AP location (44.9%, 51.1%, and 17.6%, respectively; P  < 0.001), decreased LVEF (10.3%, 6.4%, and 1.1%, respectively; P  = 0.004), and dyskinesia (16.7%, 16.0%, and 1.1%, respectively; P  < 0.001) were significantly more frequent in patients with a right or septal AP than in those with a left AP. In 31 of 50 patients with RWMA who underwent post‐RFCA echocardiography (62.0%), RWMA was completely improved after RFCA. Right AP (odds ratio [OR], 22.084; 95% confidence interval [CI], 3.628‐134.420; P  = 0.001) and dyskinesia (OR, 6.275; 95% CI, 1.186‐33.213; P  = 0.031) were significantly associated with the absence of RWMA improvement after RFCA. Conclusions: AP‐related RWMA is frequent in patients with right or septal APs. A substantial number of patients with right AP or dyskinesia may show no improvement in RWMA after RFCA.